Investigation of thermal sprayed stainless steel/WC-12wt%Co nanocomposite coatings - Chaiyasit Banjongprasert (2018)
The thermal spray coatings of stainless steel with nano-sized particles as reinforcement have been studied. Stainless steel powder mixed with 0, 2.5, 5 and 10 wt% WC-12wt%Co nano-sized powder was flame sprayed. The presence of WC-12wt%Co nano-particles in mixed powders as feedstock was confirmed. The microstructure of the coatings has been investigated using a wide range of characterization techniques: optical microscopy with image analysis, X-ray diffraction (XRD), and scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS) to understand the microstructure evolution. Chemical composition and microstructure of the coatings showed that the coatings contained stainless steel, WC, Co, and oxide layers. The addition of WC-12wt%Co increased cross-sectional hardness, reduced porosity and friction coefficient. The improved wear properties demonstrate a high potential for industrial applications of stainless steel/WC-12wt%Co coatings. © (2011) Trans Tech Publications.